MODEL PEMBELAJARAN BLENDED LEARNING: KAJIAN META-ANALISIS - Ainur Rohmawati; Iis Holisin; Febriana Kristanti (IKIP Siliwangi, 2021)
This study aims to determine the effect of the blended learning model on mathematics learning. This research method uses a systematic literature review by reviewing and analyzing 13 scientific articles downloaded through the Google Scholar platform. The results of the meta-analysis showed that the blended learning model had an effect on mathematics learning from the subject of education level, blended learning was more effective for elementary school students, than junior high, high school, and PT. This is indicated by the effect size value for elementary school level of 1.46. Learning materials that have a high influence are used on flat-sided building materials with an effect size value of 1.71. On the subject of the media used is more influential when using google classroom and edmodo media, it can be seen with the resulting effect size values of 1.71, and 1.52. In addition, the blended learning model has a high effect on the dependent variable of mathematical literacy and mathematical communication ability, this is indicated by the effect size value of the two variables of 1.71.